PENGGUNAAN FITUR MEDIA SOSIAL LIVE DAN ADS DALAM PROMOSI PRODUK BISNIS - Canra Permadi; Agi Gifari (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
Indonesia has a large population of 257 million people and Indonesia also has a considerable social-media users as much as 80 percent. Social Media used is quite diverse so that social media becomes one of the great potential to promote business products. the features used in promoting the business are the Live streaminging feature and the Advertisement manager feature. These features have the benefits of affordable prices, wide reach, market segmentation, increasing sales and measuring success in promoting a product. Success can be measured through awareness, consideration and conversation. This success can be seen through engagement, conversion and return on investment which is the basis of the benefits of a business product promotion.